Assessment of municipal solid waste settlement models based on field-scale data analysis - Kwak, Seungbok, author; Bareither, Christopher A., advisor; Shackelford, Charles D., committee member; Hess, Ann M., committee member (Colorado State University. Libraries, 2014)
An evaluation of municipal solid waste (MSW) settlement model performance and applicability was conducted based on analysis of two field-scale datasets: (1) Yolo and (2) Deer Track Bioreactor Experiment (DTBE). Yolo data were used to assess a multi-layer immediate settlement analysis and model applicability to represent compression behavior in conventional and bioreactor landfills. The DTBE included four waste layers constituting a composite waste thickness. Settlement data for each waste layer were simulated to assess variation in model parameters, and a composite waste settlement prediction was completed via applying average DTBE model parameters to each waste layer and summing settlement to represent measured settlement at the top of the waste column. The multi-layer immediate settlement analysis developed for Yolo provides a framework to estimate the initial waste thickness and waste thickness at end-of-immediate compression. An empirical estimate of the immediate compression ratio (Cc' = 0.23) combined with precompression stress (10 to 15 kPa) and recompression ratio = 1/10·Cc' yielded the target immediate settlement for the Yolo test cells. A precompression stress and recompression ratio may need to be included when using empirical estimates of Cc' to predict under small vertical stress (e.g., less than 15 kPa). Simulation of the Yolo test cells with all settlement models via least squares optimization yielded high coefficient of determinations (R2 > 0.83). However, empirical models (power creep, logarithmic, and hyperbolic) are not recommended for use in MSW settlement modeling due to non-representative long-term MSW behavior, limited physical significance of model parameters, and the requirement of measured data to determine model parameters. Settlement models that combine mechanical creep and biocompression into a single mathematical function (i.e., Gibson and Lo and Chen-2010) are formulated to constrain all time-dependent settlement to a single process with finite magnitude, which limits model applicability. Overall, all other models used in this analysis, which either have the capability to simulate complete MSW compression behavior (Sowers, Marques, Babu, Chen-2012) or where an immediate compression component can be added to the model (Gourc and Machado), were shown to provide accurate simulations and predictions of field-scale datasets. The Gourc model included the lowest number of total and optimized model parameters and yielded high statistical performance for the DTBE prediction (R2 = 0.99). The Gourc model was also found to be the most applicable and straightforward to implement and is recommended for use in practice. All other models that included unique functions for immediate compression, mechanical creep, and biocompression (Machado, Sowers, Marques, Babu, and Chen-2012) are capable of yielding satisfactory MSW simulations and predictions; however, additional model and/or model constraints are necessary for implementing these models.
Keywords: biocompression; field-scale data; immediate compression; mechanical creep compression; municipal solid waste; settlement